The paradigms of heutagogy and cybergogy in the transdisciplinary perspective - Sumarsono, Sumarsono (Universitas Pendidikan Ganesha, 2019)
Now we are entering an era where learning and teaching strategies are determined by learners. The interconnection of heutagogy independent learning strategies with internet cybergogy network learning in a transdisciplinary perspective is intended to provide a climate of learning communication between learners and instructors more broadly without being insulated by space and time. Heutagogy models provide opportunities for learners to explore knowledge and experience through more varied learning strategies so that they become more literate and relevant in the present context. This research uses the literature review method from national and international reputable journals, Elsevier, google scholar, Scopus journal, IEEE journal in searching relevant research data through the stages of review, study, structured evaluation, classification and categorization of evidence-based that has been there. In this paper, we look at the prospects and challenges of heutagogy independent learning integrated with online learning cybergogy. Several learning paradigms are proposed as a result of a literature review on the strategy of implementing heutagogy and cybergogy in a transdisciplinary perspective in Higher Education in Islamic Religious Affairs.